Krigen i Kaukasus: Baggrund, dynamik og internationale perspektiver - Hans Mouritzen; Karsten Jakob Møller; Jørgen Staun (Danish Institute for International Studies (DIIS), 2009)
The war in Caucasus from 7 to 12 August 2008 gave rise to forceful international reactions and made commentators talk about the possibility of a new 'Cold War' between Russia and the West and the 'return of history' (the fall of the Berlin Wall allegedly being the 'end of history'). At the time of writing, the pessimistic scenario seems not very likely; however, it is still energetically disputed between Russia and Georgia, who should be blamed for the initiation of war events. In this DIIS Working Paper, we seek to clarify this question along with the more complex historical backgrounds of events. the decision-making processes in Tbilisi and Moscow are analysed, and the Western diversified reactions to the conflict are described and explained. Finally, a status is made one year after the war.
Keywords: 330